THE THEME OF AMBITION MACBETH PLAY - Rafed Kawan Mohammed; Waad Adil Lateef; Liwaa Ahmed Abdullah (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
In this research, we wanted to show that Shakespeare in writing Macbeth, shows the bad side of the human being and the factors that help to increase the ambition and evilness inside man. Among these factors is Macbeth's ambition which blinded him from seeing the bloody future. This paper is divided into three sections with a conclusion; section one deals with Shakespeare's life and his work. Section two is devoted to Macbeth, the play, and the source of Macbeth than the conclusion that summarizes the findings of the paper.